Estudo da resistência à corrosão do aço inoxidável duplex saf 2205 envelhecido, em solução Nacl 3,5% - Queiroz Junior, Francisco Walfredo de (Universidade Federal Rural do Semi-Árido, 2017)
The duplex stainless steels show biphasic microstructure (ferrite and austenite), and stands out by the excellent combination of their mechanical properties and resistance to corrosion. However, when subjected to high temperatures may exhibit in its structure intermetallic phases that degrade its properties and limit its use. In this way, the objective of this work is to evaluate the corrosion resistance of SAF 2005 duplex stainless steel, as well as the effect of temperature and time of heat treatment on the corrosion resistance of steel. In order to analyze the behavior of this steel after heat treatments of aging at temperatures between 500ºC and 700ºC, for times of 6, 12 and 27 hours, by optical microscopy and potentiodynamic polarization test. Optical microscopy was utilized to observe the formation of precipitates in the microstructure and the polarization curves to evaluate the corrosion resistance. It was inferred that under the aging conditions imposed the increase in time and temperature in the heat treatment reduces the corrosion resistance of SAF 2025 duplex steel
Monografia
Keywords: Aço inoxidável duplex; Tratamento térmico; Curvas de polarização; Stainless steel duplex; Heat treatment; Polarization curves; ENGENHARIAS::ENGENHARIA MECANICA